Influence of Culture on Students' Awareness of How and Why They Learn - Choy, Siew Chee; Sedhu, Daljeet Singh; Liew, Yow Lin; Malenee, Audrey; Anuar, Norkhadirah; Lee, Mun Yee (Universiti Utara Malaysia Press, 2015)
Purpose - The reason many Asian students find student-centred learning challenging may be due to cultural factors present in every human interaction between individuals. This study attempts to determine the influence of these cultural factors on students' awareness of how and why they learn. Method - A sample of 12 students enrolled in a two year diploma course in a Malaysian university was interviewed, using a semistructured interview protocol, on the students' perceptions and experiences when learning. The results were analysed qualitatively using the interpretive approach. Findings - The results show that students rely on their teachers for information, implying a high power distance as well as low individualism, and are not inclined to explore on their own. These students readily approach their friends rather than teachers for help with their assignments. They also hold their parents' opinions in high regard. Significance - The results of this study are important for teachers when implementing student-centred learning. It will be challenging for Malaysian students to respond well to this form of learning strategy as it requires a certain amount of independent learning as well as risk-taking behaviour which these students seem to lack.